The role of vitamin D supplementation for primary prevention of cancer: meta-analysis of randomized controlled trials. Issue 6 (2nd November 2019) - Haykal, Tarek; Samji, Varun; Zayed, Yazan; Gakhal, Inderdeep; Dhillon, Harsukh; Kheiri, Babikir; Kerbage, Josiane; Veerapaneni, Vijaysai; Obeid, Michele; Danish, Rizwan; Bachuwa, Ghassan
ABSTRACT: Background : In the USA cancer is the second leading cause of mortality, as such, primary prevention of cancer is a major public health concern. Vitamin D supplementation has been studied as a primary prevention method for multiple diseases including cardiovascular disease, osteoporosis, diabetes mellitus and cancer. The role of Vitamin D as primary prevention of cancer is still controversial. With fast emergence of large randomized controlled trials (RCTs) in that regards, we aimed to evaluate the efficacy of Vitamin D supplementation as primary prophylaxis for cancer. Methods : A comprehensive electronic database search was conducted for all RCTs where comparison of Vitamin D supplementation versus placebo for the prevention of any type of disease with at least 3 years of Vitamin D supplementation was used and where cancer incidence or mortality was reported. The primary outcome was cancer-related mortality and cancer incidence. We calculated risk ratios (RRs) and 95% confidence intervals (CIs) using a random-effects model at the longest follow-up. Results : We included 10 RCTs with 79, 055 total patients, mean age of 68.07 years, a female percentage of 78.02% and a minimum follow-up of 4 years and more. Vitamin D was associated with significant reduction of cancer-related mortality compared with placebo (RR 0.87; 95% CI: 0.79–0.96; P = 0.05: I 2 = 0%). Compared with placebo, Vitamin D was not associated with significant reduction of cancer incidence (RR: 0.96; 95% CI: 0.86–1.07; P = 0.46; I 2 = 31%). Conclusion : With inclusion of studies, which did not primarily examine vitamin D for the purpose of preventing cancer or reducing cancer mortality our meta-analysis highlights that the use of vitamin D supplementation for primary prevention of cancer is encouraged as it does possibly decrease cancer-related mortality once cancer is diagnosed; however, it has no role or effect on cancer incidence.